Digitalization of Purchasing Processes in a Materials Management –Organization - Kalliokoski, Kia (My University, 2019)
Organizations all around the world are participating in the digital transformation. Distinctly, as digitalization is also affecting the supply chain performance, ways of gaining competitive advantage as well as changing the level of expertise required, this thesis investigates how the case company in question and related Materials Management –organization could utilize digitalization in operational purchasing with the support of McKinsey’s Next Generation Operating model and also how human resources needs to be considered when new ways of working are implemented in to the existing processes. The literature review of this research addresses the key definitions related to supply chain management, operational purchasing process and digitalization as a phenomenon required to understand the empirical part and related findings. Also, the concept of McKinsey’s Next Generation operating model and the five approaches needed in implementing digital technologies are explained. The five approaches are digitization, intelligent process automation, business process outsourcing, advanced analytics and lean process redesign. In the center of attention in the results of this thesis is the core purchasing process in operational purchasing of the case company. The empirical part of this research investigates the utilization status of digitalization in the existing process and based on the findings a proposal for development is introduced containing a set of suggestions for using predictive analytics in forecasting, utilization of RPA in balancing rescheduling of purchase orders and a platform for improving quality of communication. Finally, taking into consideration the human resource aspect of the study, a theoretical model for human resource development program is reviewed that can be implemented concurrently with the development proposals to make sure that personnel is gaining the needed competence and knowledge.
Keywords: Digitalization, Purchasing, Digital Supply Chain; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management